Initial Bacterial Adhesion and Biofilm Formation on Aligner Materials - Sibel Tektas; Thomas Thurnheer; Theodore Eliades; Thomas Attin; Lamprini Karygianni (MDPI AG, 2020)
The present study aims to assess the initial bacterial adhesion and biofilm formation on different aligner materials. A total of four different aligner materials, CA-medium (CAM), copolyester (COP), Duran (DUR), Erkodur (ERK), were tested. Stimulated human saliva was obtained from six healthy volunteers. Salivary bacteria were harvested by centrifugation, and 1 mL of the salivary suspension was injected onto each sample surface for 2 h and 3 days, respectively. The samples were then washed twice with 5 mL 0.9% NaCl solution, and non-adherent bacteria were removed. The adherent microorganisms were dislodged from the sample surfaces after ultrasonication for 4 min in 1 mL 0.9% NaCl on ice. After the incubation of the adherent salivary bacteria under both aerobic and anaerobic conditions on Columbia blood agar plates at 37 °C and 5% CO2 and in anaerobic jars overnight, several dilutions thereof were used for the determination of CFUs. This protocol was applied three times, obtaining an average of nine independent measurements for each material group. Overall, the differences between the tested aligner materials as well as between the materials and controls were not of statistical significance (p > 0.05). Regarding initial bacterial attachment and biofilm formation, the tested aligner materials are comparable to enamel and metal orthodontic brackets and can be therefore considered for clinical use. The four tested aligner materials CAM, COP, DUR, ERK showed no significant differences in initial microbial attachment and biofilm formation of aerobic and anaerobic species compared to enamel and conventional brackets.